Pengukuran Tekanan Intra Abdominal Sebagai Penanda Toleransi Nutrisi Enteral pada Pasien ICU - Sany, Puti Rahmitha; Dahlia, Debie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This aim of this study is to determine the effectiveness of intra-abdominal pressure measurement as a marker of enteral nutrient tolerance in ICU patients. The method of this study used systematic review searched several eligible research articles from October 2013 to October 2023 using Scopus, ProQuest, Science Direct, and PubMed databases with the keywords critical ill patient, intra abdominal pressure measurement, gastric residual volume, and enteral nutrition.The result of this study show that based on six eligible research articles from 5 different countries that had been identified, show that intra-abdominal pressure measurements can predict enteral nutrient tolerance, although there was one study that had low sensitivity and significance. This systematic review concluded that intra-abdominal pressure measurements is one of the effective strategies that can be used to predict enteral nutrient tolerance in adult ICU patients. Keywords: Critical Ill Patient, Intra Abdominal Pressure Measurement, Gastric Residual Volume, Enteral Nutrition